Prevalence of Sports Practice among Mexican Adults in 2002 and 2014 - Ortiz-Hernandez, L.; Ayala-Hilario, C.; Ayala- Guzmán, CI. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The aim of our study was to know the change over time of sports practice prevalence in Mexican adults and its socio-demographic correlates. We analyzed the Mexican National Survey of Time Use (ENUT) conducted in 2002 and 2014; which is based on a representative sample of Mexican adults. Through a questionnaire, it was inquired if people practised sport in the previous week of the interview and the time spent to do it. The independent variables were sociodemographic characteristics. We found that the prevalence of sports practice increased between 2002 and 2014 (from 15.8% to 29.3%). Being single or having a high socioeconomic position was associated with a higher probability of sports practice. Men and city dwellers had higher probabilities of practice sport compared with their counterparts; although these differences tended to decrease. We conclude that the prevalence of sports practice in Mexico has increased, but it remains low. We identified groups with lower probabilities to practice sport in which efforts can be focused to promote active lifestyles.